BPJS Health Patient Satisfaction in Health Services at Udayana Hospital Denpasar - Silvia Intan Wardani; Ni Luh Putu Suardini Yudhawati (Universitas Mandala Waluya, 2022)
The National Health Insurance with one of its main focuses is to increase participant satisfaction with a satisfaction target in 2020 of 85%. The quality of service received by patients includes aspects of reliability, assurance, responsiveness, tangibles, and empathy. The current problem is that there is no written report on the length of waiting time for services in hospitals The purpose of the study is to find out the relationship between service quality and patient satisfaction at Udayana Hospital Denpasar. This research is quantitative research with analytical surveys and cross-sectional research designs. The study population was 1743 people and a sample of 95 people who were patients participating in BPJS Kesehatan at Udayana Hospital Denpasar. This study used a statistical test of Pearson correlation. The results of the data analysis showed a relationship between service quality and patient satisfaction of BPJS Kesehatan at Udayana Hospital Denpasar, with a value of r = 0.419 and a significant value of p = 0.000, a significant level used by 5% (0.05). The most influential aspect is assurance which includes the availability of doctors who are experts in their fields, reliability, friendliness and courtesy of nurses. It can be concluded that the quality of service received by the patient affects the satisfaction of the patient himself. Advice for Udayana Denpasar Hospital to improve the quality of health services for all patients, especially in aspects that are still in the moderate category, namely responsiveness, reliability and tangible.